The Design and Development of Web-Based Dormitory Management System for Cagayan State University-Aparri - Bautista, Saniata (Azal Arts and Humanities, 2025)
Cagayan State University – Aparri has long relied on a manual dormitory management system, leading to recurring administrative problems such as delayed processing, record-keeping difficulties, and limited access to essential data. To address these challenges, this study developed a web-based dormitory management system aimed at streamlining processes such as student registration, room assignments, occupancy tracking, billing, and report generation. The system was designed to enhance operational efficiency, minimize errors, and offer real-time data access to administrators and residents alike. A developmental-descriptive research design was employed, using the Agile methodology to guide the system's development. Respondents were the dormitory staff and student residents and selected through purposive sampling. Data were gathered through surveys, interviews, and usability testing. Findings showed that the system greatly improved workflow, reduced reliance on manual processes, and offered a more intuitive interface for users. With positive feedback from stakeholders, the system is recommended for full deployment at CSU-Aparri and considered scalable for implementation across other CSU campuses.